Introductory Chemistry: An Active Learning Approach, 7th Edition - Mark S. Cracolice; Edward I. Peters (Cengage Learning, 2020)
Teach your course your way with INTRODUCTORY CHEMISTRY: AN ACTIVE LEARNING APPROACH, 7th Edition. This modular, student-friendly resource allows you to tailor the order of chapters to accommodate your needs, not only by presenting topics so they never assume prior knowledge, but also by including any necessary preview or review information needed to learn that topic. The authors' question-and-answer presentation, which allows students to actively learn chemistry while studying an assignment, is reflected in three words of advice and encouragement repeated throughout the book: ""Learn It Now!"" This updated 7th edition leaves no students behind. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.